(untitled) - Bowsher, Jack E. (New York, 1989)
Public education can learn from corporate training programs! Jack Bowsher, who helped control a billion-dollar-a-year budget as Director of Education at IBM (now retired), has a proven track record in education and training. This book outlines an incisive, workable program for the revival of our educational system. Bowsher takes a close look at what's wrong with our schools, and tells why many ``solutions'' don't work. He then applies the best elements of corporate education--such as incentives and accountability--to public education, arguing against blindly throwing more money and more teachers into an already troubled system.
Keywords: Giáo dục,Education; Mục đích và mục tiêu,Aims and objectives; United States